A166 INCIDENCE OF INFLAMMATORY BOWEL DISEASE IN SOUTH ASIAN AND CHINESE PEOPLE: A POPULATION-BASED COHORT STUDY FROM ONTARIO, CANADA. (4th March 2021) - Dhaliwal, J; Tuna, M; Murthy, S; Shah, B; Griffiths, A; Benchimol, E I
Abstract: Background: Studies using population-based data from Ontario previously found South Asian (SA) and East Asian immigrants develop IBD at lower rates than non-immigrants. However, incidence among the Canadian-born children of SA immigrants was comparable to those of non-immigrants, and younger age at arrival to Canada was associated with an increased risk. Aims: The primary aim of the study was to determine the incidence of IBD in South Asian and Chinese people compared with the general Ontario population. Methods: All incident cases of IBD in children (1994–2015) and adults (1999–2015) were identified from population-based health administrative data in Ontario, Canada using validated algorithms. Ethnicity was assigned by linkage of a validated surname-based database to health administrative data, immigration records, and hospital birth data. We determined standardized incidence of IBD and the adjusted incidence rate ratio (aIRR) in SAs and Chinese comparable to the general population. Based on existing evidence, we adjusted for confounders selected a priori : immigration status, sex, income and rurality. Results: Amongst 14, 483, 769 people in the general population, standardised incidence of IBD per 100, 000 person-years (PY) was 24.7 (95%CI 24.4–25.0), compared with 14.6 (95%CI 13.7–15.5) in 982, 472 SAs and with 5.4 (95%CI 4.8–5.9) in 764, 397 Chinese. The risk of IBD in SAs was lower to the general population prior to adjusting for immigration, IRR 0.82 (95%CI 0.78–0.86), but comparable after adjusting for confounders (aIRR 1.10, 95%CI 1.05–1.16). Only SA adults (18-64y) had a higher risk of IBD (aRR 1.10, 95% CI 1.02–1.18), not children or seniors. Compared to the general population, SAs had a lower risk of Crohn disease (CD), irrespective of age (aIRR 0.66, 95%CI 0.60–0.77), but a higher risk of ulcerative colitis (UC) (aIRR 1.47 (95% CI 1.34–1.61).). SAs were more likely to develop UC than CD (aIRR 1.51, 95%CI 1.38–1.66). The risk of IBD was much lower in Chinese people, irrespective of age (aIRR 0.24, 95%CI 0.20–0.28). This lower risk was similar in CD (aIRR 0.21, 95%CI 0.17–0.26) and UC (aIRR 0.28, 95%CI 0.23–0.25). The SA population had a considerably higher risk of developing IBD compared to the Chinese population (aIRR 4.29, 95%CI 3.62–5.08), and were more likely to develop UC (aIRR 1.36, 95% CI 1.08–1.73). Conclusions: Canadian SAs had a similarly high risk of developing IBD compared with the general population after adjusting for immigration status, a finding distinct from the Chinese population. There was an age-response relationship in SAs only. Furthermore, SAs were more likely to develop UC than people of Chinese origin, potentially owing to differences in genetic susceptibility and/or environmental factors. Funding Agencies: None